Impact of the national sarcoma guidelines on the prevalence and outcome of inadvertent excisions of soft tissue sarcomas: An observational study from a UK tertiary referral centre. Issue 3 (March 2022) - Fujiwara, Tomohiro; Evans, Scott; Stevenson, Jonathan; Tsuda, Yusuke; Gregory, Jonathan; Grimer, Robert; Abudu, Adesegun
Abstract: Objectives: This study aims to investigate the impact of the national guideline on the prevalence and outcome in patients with soft-tissue sarcoma (STS) who had undergone inadvertent excisions. Methods: A total of 2336 patients were referred to a tertiary sarcoma centre from six regions (North East, North West, East Midlands, West Midlands, Wales, and South West) in the United Kingdom with a diagnosis of STS between 1996 and 2016, of whom 561 patients (24.0%) had undergone inadvertent excisions. Patients were categorised into two groups of 10-year periods pre and post the National Institute for Health and Clinical Excellence (NICE) guideline implementation in 2006. Results: The proportion of inadvertent excisions decreased after the NICE guideline implementation: 27.2% (pre-NICE) versus 19.8% (post-NICE) ( p = 0.001). A substantial regional variation (17.4%–34.5%) in the proportion of inadvertent excisions in the pre-NICE era was reduced in the post-NICE era (14.3%–22.4%). The 5-year disease-specific survival was 77.7% (pre-NICE) versus 75.6% (post-NICE) ( p = 0.961) and there was a trend toward lower incidence of local recurrence in the post-NICE era; 13.5% (pre-NICE) versus 10.5% (post-NICE) ( p = 0.522). Multivariate analyses revealed that residual tumours in re-resection specimens were independently associated with an increased risk of disease-specific mortality (HR, 3.35; p < 0.001) and local recurrence (HR, 1.99; p = 0.017), which was significantly reduced after the NICE guideline implementation (53.2% versus 42.0%; p = 0.022). Conclusions: The NICE guideline implementation reduced the proportion of patients with STS who had undergone inadvertent excisions and residual tumour in re-resection specimens, indicating an improved pre-referral management of STSs.